Convective structures of salt fingers at a neutrally buoyant density interface - Singh D.K.; Singh O.P.; Nihaal K.M.; Mahabaleshwar U.S. (My University, 2025)
This paper presents a comprehensive exploration of the transient evolution of double-diffusive salt fingers within a two-layer thermohaline system, employing an advanced high-resolution numerical model. The investigation spans a wide range of Rayleigh numbers (7 × 109–7 × 103) and characterized by a density stability ratio near one, indicative of neutral buoyancy conditions. The study reveals complex finger structures in both concentration and buoyancy fields. As the Rayleigh number varies, the system undergoes a transition from being convection-dominated at high values to a diffusion-dominated state at lower Rayleigh numbers. The paper investigates the time series evolution of convective flux ratios and buoyancy, shedding light on the dynamic evolution of these phenomena. The paper further contributes an energy budget analysis specifically tailored for salt-fingering phenomena in the two-layer system. This analysis further examines the temporal evolution of potential energy, background potential energy attributed to temperature and salinity, and overall kinetic energy. A particular focus is placed on investigating the temporal evolution of excess density across the interface, offering nuanced insights into the system's behaviour. Additionally, the joint probability density function (PDF) of vertical velocity and salinity anomaly is analysed across varying Rayleigh numbers. A generalised evolution pattern of PDF is also presented to understand system’s dynamical evolution behaviour. © The Author(s), under exclusive licence to Springer Nature B.V. 2024.